Analysis of LEAC biosensor for scalable manufacturing using BPM and FDTD simulation methods - Holmes, Cameron Dane, author; Lear, Kevin L., advisor; Nikdast, Mahdi, committee member; Kipper, Matt, committee member (Colorado State University. Libraries, 2024)
The increasing demand for rapid, scalable, and accurate diagnostic tools has driven the development of optical biosensing technologies. LEAC (Local Evanescent Array-Coupled) biosensors, which leverage the evanescent field generated by optical waveguides, are particularly well-suited for applications in biomedical diagnostics, environmental monitoring, and point-of-care testing. LEAC biosensors have previously been fabricated in incomplete and unoptimized near-commercial CMOS processes and fully custom processes in a university cleanroom but have not been implemented in suitable high-volume processes such as commercial silicon photonics. A primary motivation for the research presented in this thesis is to evaluate the ability to fabricate LEAC biosensors operating at 1550 nm wavelengths in the commercial AIM Photonics' active silicon photonics process. This thesis presents a comprehensive tolerance analysis of LEAC sensors for both bulk sample layers (400 nm thick) and protein monolayers (10 nm thick) in AIM's process, focusing on the impact of variations in key design parameters—specifically waveguide core thickness, cladding layers, and photodetector placement—on sensor sensitivity. Beam Propagation Method (BPM) and Finite-Difference Time-Domain (FDTD) simulation techniques are employed to assess how these tolerances affect optical field propagation, power dissipation, and flux into the photodetector, serving as proxies for sensor performance. Additionally, the study examines crosstalk between multiple sensing regions, evaluating how refractive index variations in one region influence adjacent regions—an important consideration for multi-region sensors. Results show that sensor sensitivity increases with cladding thickness and decreases with waveguide core thickness. A 25 nm manufacturing error in core thickness resulted in less than a 10% sensitivity shift, and a 300 nm cladding thickness error had a similarly small effect. Resonant absorption between the core and photodetector was observed across both bulk and monolayer samples. Sensitivity depends heavily on proximity to resonance; a 10% error in photodetector thickness at resonance caused a 600% change in sensitivity, while off-resonance, the same error had minimal impact. Coupled Mode Theory (CMT) explained these energy transfers and power fluctuations. ANOVA analysis of full-device FDTD simulations quantified forward crosstalk due to modulated absorption from sample regions closer to the optical source (upstream). Forward crosstalk was found to be negligible for protein monolayer samples but could be significant in bulk samples. However, even in bulk samples, forward crosstalk was largely mitigated using photocurrent ratios with a reference region. A crosstalk ration was used as a metric to determine the influence of each refractive index (n1, n3) on the photocurrent ratio. In the forward crosstalk direction, the use of photocurrent ratios decreased the magnitude of the forward crosstalk ratio; however, the use of photocurrents inherently introduce dependance on downstream indices (reverse crosstalk). Reverse crosstalk, caused by reflections at the dielectric boundary between sensing regions, was found to be negligible using photocurrent ratios with bulk analytes; however, with monolayers, the use of photocurrent ratios introduced a slight dependence on the downstream region, indicating minor backward crosstalk. This can be mitigated by using raw current values rather than current ratios. Raw currents eliminate backward crosstalk in region 1, while photocurrent ratios effectively eliminate forward crosstalk in region 3.
Keywords: biological sensing; finite difference time domain; tolerance analysis; crosstalk; beam propagation method; optoelectronics